Death, bereavement and grief: the role of the teacher in supporting a child experiencing the death of a parent. Issue 2 (3rd July 2021) - Dimery, Eleanor; Templeton, Sian
ABSTRACT: Experiencing the death of a parent as a child can have substantial implications on their present and future life. The nature of grief is complex, with many contextual factors influencing the child's management. This study explores the teacher's role in supporting a child bereaved of a parent through the use of interviews with three teachers who have supported a bereaved child. Using the themes that emerged from the literature and interviews, a questionnaire was disseminated, with 16 individuals reflecting on their experience of a parental death whilst in school. The results reveal informed views from teachers in relation to the vital role that they can play in supporting a bereaved child. Responses from bereaved individuals offer guidance on how school staff might offer support and understanding in these circumstances. Overall, the study suggests that teachers have a significant role in the child's management of their grief. Despite a lack of initial teacher training in the area of loss, often their small, dynamic forms of support, such as listening and taking a genuine interest in the child, along with supportive proactive school approaches, are what makes a difference to the child effectively managing their grief.